Current Trends in Whey Processing - Korotkiy I.; Plotnikov I.; Maseeva I. (Техника и технология пищевых производств, 2019)
The integrated use of secondary raw milk is one of the most effective ways to optimize the processing of raw materials in the production of dairy products. The unique composition and properties of curd whey makes it a valuable industrial raw material that can be processed into a variety of foods and feed products. Nowadays, whey protein concentrates (WPC) are extremely popular with consumers. One of the promising areas of industrial processing of acid whey is the extraction of proteins by means of separate freezing (cryoconcentration). This process takes place at low temperatures (from 0 to minus 15°C), which makes it possible to preserve the composition and properties of the raw material, prevents denaturation of whey protein fractions, and preserves its valuable thermolabile components. The authors conducted laboratory tests of curd whey and WPC produced by several dairy companies. The research allowed the authors to determine the composition, sensory, physico-chemical, and microbiological properties of the samples. The research objective was to evaluate the sensory properties of the initial cheese whey and WPC obtained by cryoconcentration, to establish their chemical composition, as well as physico-chemical and microbiological parameters. The research also featured the effect of the whey acidity on the WPC output and the development of technological schemes of WPC production by separate freezing. All the samples of curd whey proved to meet the current standards and can be used for WPC production. The sample of laboratory-obtained WPC sample had 20.19% of dry substances and 12.80% of protein, which corresponds to the standard albumin with its 20.0% of dry substances. The titratable acidity of WPC did not exceed the permissible level of 95°T. The experimental results proved that the cryoconcentration technology produced concentrate that met the requirements of regulatory and technical documentation. The obtained data revealed an increase in titratable acidity from 47°T to 50°T during the storage of curd whey for 7 days. The increase in acidity increased the yield of WPC after 7 days of serum storage by 57.6%. The new WPC production scheme consisted of several stages: (1) the whey was obtained; (2) casein dust and dairy fat were excluded; (3) pasteurization; (4) two-stage cryoconcentration; (5) thermal coagulation of whey concentrate; (6) separation of WPC. The technology of cryoconcentrationcurd whey suggests designing industrial installations in-line type to obtain CSB.